The Impact of Influencer Marketing and Online Customer Reviews on Purchase Decisions of Facetology Sunscreen among TikTok Users - Derika Nuryanti; Rizky Ferrari Octavian; Farid Arifin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid growth of social media has changed consumer behavior in searching for information and making purchasing decisions. TikTok has become one of the most popular platforms for product promotion through influencer marketing and online customer reviews. This study aims to analyze the influence of Influencer Marketing and Online Customer Reviews on the Purchase Decisions of Facetology Sunscreen products among TikTok users. This research employs a quantitative approach using a survey method. Data are collected through questionnaires distributed to TikTok users who are familiar with Facetology Sunscreen products. The data are analyzed using multiple linear regression to examine the partial and simultaneous effects of the independent variables on purchase decisions. The study is expected to provide empirical evidence regarding the role of influencer marketing and online customer reviews in shaping consumer purchase decisions. The findings are expected to contribute to the development of digital marketing strategies, particularly for skincare brands that utilize social media platforms to increase consumer engagement and purchasing behavior.